Прояви існування колективного переносу в атомарних рідинах та рідких металах - Makhlaichuk, V.M. (Publishing house "Academperiodika", 2021)
The behavior of the effective radii of “particles” (molecules and ions) as a manifestation of the collective components of their thermal motion in atomic liquids and liquid metals has been studied. The specific form of the temperature dependence of the effective radii of molecules and ions is established in good agreement with the results obtained for the hydrodynamic radii according to the Stokes–Einstein formula. Attention is drawn to the differences between the values of the radii of particles that are used to describe the thermodynamic and kinetic properties of liquids.